2015
DOI: 10.1145/2808691
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Computer Intrusion Detection Systems

Abstract: The evaluation of computer intrusion detection systems (which we refer to as intrusion detection systems) is an active research area. In this article, we survey and systematize common practices in the area of evaluation of such systems. For this purpose, we define a design space structured into three parts: workload, metrics, and measurement methodology. We then provide an overview of the common practices in evaluation of intrusion detection systems by surveying evaluation approaches and methods related to eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 176 publications
(81 citation statements)
references
References 48 publications
0
80
0
1
Order By: Relevance
“…To the best of our knowledge, this is the first paper that aims at systematically understanding and analyzing the root causes of intrusion detection false-negatives, with the ultimate goal of drawing new insights and principles to guide the design of the next generation IDSs. This is true despite the recent resurgence in studying IDSs (see, for example, [2], [9], [11], [12], [13], [14] and the references therein). In a broad sense, the present study falls into the broader field of cybersecurity data analytics [15], [16], [17], [18], [19], [20].…”
Section: B Related Workmentioning
confidence: 99%
“…To the best of our knowledge, this is the first paper that aims at systematically understanding and analyzing the root causes of intrusion detection false-negatives, with the ultimate goal of drawing new insights and principles to guide the design of the next generation IDSs. This is true despite the recent resurgence in studying IDSs (see, for example, [2], [9], [11], [12], [13], [14] and the references therein). In a broad sense, the present study falls into the broader field of cybersecurity data analytics [15], [16], [17], [18], [19], [20].…”
Section: B Related Workmentioning
confidence: 99%
“…In order to examine the bias of the naïve estimators given by Eqs. (8)- (12), we need to investigate their asymptotic distributions. For this purpose, we make the following assumption:…”
Section: Investigating Statistical Properties Of Naïve Estimatorsmentioning
confidence: 99%
“…Kührer et al [6] focused on the effectiveness of malware blacklists and showed that the current blacklist is insufficient to protect against the variety of malware threats. There are other studies focused on evaluating the strength of IDS or other security products [7,8], strength of user password [9,10], and so on. However, the effects of all the metrics mentioned above are not ideal when faced with unknown threats.…”
Section: Related Workmentioning
confidence: 99%